INNOVATIVE TECHNOLOGIES FOR TEACHING CHEMISTRY - Tadjieva Khosiyat Sultanovna (Modern American Journals, 2025)
In the most rapidly developing industries, which undoubtedly include the chemical and pharmaceutical industries, the demand for highly qualified specialists is constantly growing. This growth is driven by the increasing development of new products, innovative unique technologies, and the use of modern equipment, as well as the computerization of many production processes. This creates an urgent need to review existing educational technologies and integrate modern information and communication technologies into the educational process. In the current situation, the most appropriate form of organizing the educational process is e-learning, the primary objective of which is to elevate the quality of educational services related to the training, retraining, and advanced training of specialists in the chemical and pharmaceutical industries. Since many chemical and pharmaceutical corporations have numerous branches and representative offices worldwide, organizing training for personnel from different countries becomes challenging. Furthermore, there is a need to conduct training quickly so as not to limit the implementation of innovative technologies and the sale of new products. From this perspective, e-learning is one of the most effective methods of training, retraining, and advanced training of personnel.